DETECTION OF STROBOSCOPIC EFFECT USING CONTROLLED LED FLICKERING - Apryandi, Handy
The widespread use of LED has raised concerns about possible negative impacts on human health. Temporal Light Modulation (TLMs) in which the stroboscopic effect included in it, has been widely discussed and assessed performance, health, and in terms of the safety aspect. Stroboscopic Effect Visibility Measure (SVM) was developed to provide an assessment of the stroboscopic effect. An electronic system is used to assist in detecting stroboscopic effects by setting parameters (frequency and duty cycle) to create flickering light conditions. By adding the level confidence from participants to the observation of the stroboscopic effect can expand the assessment of the threshold of visibility, with more optimal results.